Novel insights into osteocyte and inter-organ/tissue crosstalk - Zhang, Yan; Chen, Qingchang (Frontiers in Endocrinology, 2024)
Osteocyte, a cell type living within mineralized bone matrix and connected with each other by means of numerous dendrites, appears to play a major role in body homeostasis.Benefit from the maturation of osteocyte extraction and culture technique, many crosssectional studies have been conducted as a subject of intense research recent years, illustrating the osteocyte-orgran/tissue communication not only mechanically but also biochemically. The present review comprehensively appraises the newly research work of possible crosstalk between osteocyte and closely situated or remote vital organs/tissues. We aim to bring together recent key advances and discuss the mutual effect of osteocyte and brain, kidney, vascular calcification, muscle, liver, adipose tissue and tumor metastasis and elucidate therapeutic potential of osteocyte.